WORKSHOP STRATEGI PUBLIKASI KARYA ILMIAH DI JURNAL ILMIAH - Rosdianto, Haris; Murdani, Eka; Sulistri, Emi; Anitra, Rien; Sumarli, Sumarli; Utama, Erdi Guna; Wijaya, Andika Kusuma (Jurnal Pengabdian Masyarakat Khatulistiwa, 2024)
ABSTRACTThe community service that has been carried out is a workshop on strategies for publishing scientific works in scientific journals for Singkawang city science teachers. The objectives of this service activity are: (1) providing material regarding knowledge in how to write to publish scientific articles in research journals; (2) providing training in writing and publishing scientific articles. The focus of this service is to provide information to teachers so that they have an understanding in writing scientific papers in both quantitative and qualitative research methods; provide material on strategies for finding correct and relevant scientific journals so that they are recognized in the assessment of teachers' functional positions; provide material on how to send scientific paper manuscripts to scientific journals until the manuscript is accepted. The methods used in this scientific work publication workshop are: 1) planning; 2) implementation; and 3) reflection. Evaluation of activities is carried out through: 1) Question and answer; 2) Google form related to the questionnaire to measure teacher understanding and responses regarding material content and workshop effectiveness. Indicators of success in implementing scientific work publication workshops use 2 methods, namely: (1) evaluation during the activity process, and (2) evaluation after the workshop activity. Keywords: Scientific articles, writing, community service. ABSTRAKPengabdian pada masyarakat yang telah dilakukan adalah kegiatan workshop strategi publikasi karya ilmiah di jurnal ilmiah bagi guru di kota Singkawang. Tujuan kegiatan pengabdian ini yaitu: (1) memberikan materi mengenai pengetahuan dalam cara penulisan artikel ilmiah dan cara mempublikasikan artikel ilmiah di jurnal penelitian;         (2) memberikan pelatihan penulisan dan publikasi artikel ilmiah. Adapun fokus pada pengabdian ini yaitu memberikan informasi kepada guru agar memiliki pemahaman dalam menulis karya ilmiah yang baik dan benar baik di metode penelitian kuantitatif maupun kualitatif; memberikan materi tentang strategi menemukan jurnal ilmiah yang benar dan relevan agar diakui dalam penilaian jabatan fungsional guru; memberikan materi tentang cara mengirim naskah karya ilmiah pada jurnal ilmiah yang sudah didapatkan sampai naskah tersebut dinyatakan diterima (accepted) oleh editor. Metode yang digunakan dalam kegiatan workshop publikasi karya ilmiah ini yaitu: 1) perencanaan; 2) pelaksanaan; dan 3) refleksi. Evaluasi kegiatan dilakukan melalui: 1) Tanya jawab. 2) Google form terkait kuesioner untuk mengukur pemahaman dan respon guru mengenai konten materi dan efektivitas workshop. Indikator keberhasilan dalam pelaksanaan workshop publikasi karya ilmiah menggunakan 2 metode, yaitu: (1) evaluasi selama proses kegiatan, dan (2) evaluasi pasca kegiatan workshop.Kata Kunci: Karya ilmiah, penulisan, pengabdian kepada masyarakat